Implementation of “Outbound Green Class” Program as a Way to Increased English Language Ability and interest of reading activity for Children and Adolescents at Makassar City - Musdalifah Ifah Rahman; Ismaya Ismaya; Elihami Elihami (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2020)
Community Service Activities (PKM) about “Outbound Green Class” program was one of the newest programs that the author applied in her English course place. She carried out this activity in collaboration with several her friends and who have same profession with her that was English lecturer. "Outbound Our Green Class" program provided a brief description of the guidance process increased English learning skills and interest to do reading activity with used the principle "English was cheap and could be learned anywhere and anytime". In this community service (PKM) activity, English was one of the fields of knowledge that would be specialized or studied. Children and adolescents who came from poor parents' economies were the second material to be specialized or studied in this community service activity (PKM) about English tutoring using the principle "English was cheap and could be learned anywhere and anytime". Some of the goals or functions of this community service activity (PKM) were in accordance with the principle "English was cheap and could be learned anywhere and anytime", namely: the first purpose or function, to show the world, especially to the wider community, especially children and adolescents who speak English. English was not difficult, and not as scary as a monster. The second purpose or function was to help children and adolescents who came from poor parents' economies to learn English at no charge and help prepared themselves to implement the "AFTA" program, which provided a great opportunity for all Indonesian citizens to work. And the third purpose or function was to foster enthusiasm of learning English for children and adolescents in Makassar city.